1990
DOI: 10.4319/lo.1990.35.8.1781
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate use by plankton in the eastern subtropical North Atlantic, March‐April 1989

Abstract: Nitrate concentration was measured in seawater samples from the euphotic zone at the beginning and end of 12‐h, daytime, in situ incubations. The changes in concentration are considered to be measurements of new production. During periods of 2–3 weeks in March–April 1989, important time scales for NO3− input to the euphotic zone (i.e. residence times) and new production were ~26 d at 18°N, 31°W and ~10 d near 33°N, 21°W. The average rate of NO3− use in the two areas was 2.63 and 0.62 mmol N m−2 (12 h)−1, or, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…À uptake with depth, are a common observation in subtropical waters [e.g., Eppley and Koeve, 1990;Eppley and Renger, 1992;Allen et al, 1996;Varela et al, 2005]. However, as light-dependent photosynthetic rates are typically highest in surface waters [Maranon et al, 2000;Poulton et al, 2006], there is a vertical separation between the region of the water column primarily involved in NO 3 À uptake and that involved in carbon fixation.…”
Section: Nitrate Uptakementioning
confidence: 99%
See 1 more Smart Citation
“…À uptake with depth, are a common observation in subtropical waters [e.g., Eppley and Koeve, 1990;Eppley and Renger, 1992;Allen et al, 1996;Varela et al, 2005]. However, as light-dependent photosynthetic rates are typically highest in surface waters [Maranon et al, 2000;Poulton et al, 2006], there is a vertical separation between the region of the water column primarily involved in NO 3 À uptake and that involved in carbon fixation.…”
Section: Nitrate Uptakementioning
confidence: 99%
“…[15] Previous examples of high NO 3 À uptake, or uptake in excess of local production requirements, at the nitracline are known [Eppley and Renger, 1986;Eppley and Koeve, 1990;Eppley and Renger, 1992;Allen et al, 1996;Varela et al, 2005]. Suggested causes for this observation include (1) heterotrophic bacterial uptake [Eppley and Renger, 1992], (2) transiently or permanently decoupled algal C:N uptake ratios [Eppley and Renger, 1986;Banse, 1994;Anderson and Pondaven, 2003;Falkowski and Davis, 2004;Christian, 2005], (3) uptake by vertically migrating species of phytoplankton such as Rhizosolenia spp.…”
Section: Deep Nitrate Uptakementioning
confidence: 99%
“…At the base of the euphotic zone, however, a number of studies have reported enhanced rates of nitrate uptake indicative of algal growth on a deep nitrate (NO 3 − ) reservoir (King & Devol 1979, Le Bouteiller 1986, Lewis et al 1986, Eppley & Koeve 1990, Painter et al 2007). Infrequent observation of this NO 3 − uptake maximum has not prevented recognition of a deep perennial layer of new production in the subtropical ocean (Ward et al 1989, Harrison 1990).…”
Section: Introductionmentioning
confidence: 99%
“…A recently reported unexpected nitrate distribution in the euphotic zone (EPPLEY and KOEVE, 1990) at 18°N, 30°W has been related to the occurrence of subsurface salinity maximum water at the base of the euphotic zone (PODEWSKI et al, 1993). In this paper wc attempt to relate observed variability in new production rates in the area (EPPEEY el a[.. 1990;EPPLEY and KOEVE, 1990) to hydrographical and chemical patterns within the uppe, r 200 m which were influenced by the frequent occurrence of Sm~ × water.…”
mentioning
confidence: 99%
“…In this paper wc attempt to relate observed variability in new production rates in the area (EPPEEY el a[.. 1990;EPPLEY and KOEVE, 1990) to hydrographical and chemical patterns within the uppe, r 200 m which were influenced by the frequent occurrence of Sm~ × water.…”
mentioning
confidence: 99%